Producing territory: territorial organizing of movements in Buenos Aires. - Mason-Deese, Liz; Habermehl, Victoria; Clare, Nick (Geographisch-Ethnographische Gesellschaft Zürich, 2019)
In this paper we analyze the territorial organizing of two dissimilar social movements across Greater Buenos Aires, showing how urban struggles produce territory as a key element of their political practice. Through their relational, contested character, these Latin American territories foreground an alternative to state-centric, Anglo-American models of territorial politics. First, the unemployed workers' movements in the urban periphery show how the territorial organization of production and reproduction creates new social relations, and second, an assembly-organized market emphasizes the relationality of territory in constructing solidarity economies. This paper contributes to debates on urban social movements by showing that these movements use practices of territorial organizing to produce urban territory in distinct ways, and that territorial organizing is relational, contested, and central to movements' praxis.
Keywords: Stadtsoziologie; Sozialbewegung; Sozialer Konflikt; Stadtgeographie; Wirtschaftskrise; Selbstversorgung; Selbstorganisation; Stadtquartier